Artificial dermal substitutes for tissue regeneration: comparison of the clinical outcomes and histological findings of two templates. Issue 8 (August 2020) - De Francesco, Francesco; Busato, Alice; Mannucci, Silvia; Zingaretti, Nicola; Cottone, Giuseppe; Amendola, Francesco; De Francesco, Marialuisa; Merigo, Flavia; Riccio, Valentina; Vaienti, Luca; Parodi, Pier Camillo; Sbarbati, Andrea; et al.
Objective: Artificial dermal substitutes (DSs) are fundamental in physiological wound healing to ensure consistent and enduring wound closure and provide a suitable scaffold to repair tissue. We compared the clinical and histological features of two DSs, Pelnac and Integra, in the treatment of traumatic and iatrogenic skin defects. Methods: This prospective observational study involved 71 randomly selected patients from our hospital. Wound healing was analyzed using the Wound Surface Area Assessment, the Vancouver Scar Scale, and a visual analog scale. Histological and immunohistochemical evaluations were also performed. Results: At 2 weeks, greater regeneration with respect to proliferation of the epidermis and renewal of the dermis was observed with Pelnac than with Integra. At 4 weeks, the dermis had regenerated with both DSs. Both templates induced renewed collagen and revascularization. Differences in the Vancouver Scar Scale score were statistically significant at 4 weeks and 1 year. Pelnac produced a significant increase in contraction at 2 weeks with increasing effectiveness at 4 weeks. Integra produced a higher percentage reduction in the wound surface area and a shorter healing time than Pelnac for wounds >1.5 cm deep. Conclusion: Our observational data indicate that both DSs are effective and applicable in different clinical contexts.